1991
DOI: 10.2527/1991.691276x
|View full text |Cite
|
Sign up to set email alerts
|

Prepubertal changes in plasma FSH and inhibin in Holstein bull calves: responses to castration and(or) estradiol.

Abstract: The objectives of two studies were to detennine 1) whether plasma concentrations of inhibin (INH) changed with age in prepubertal bulls and whether these changes were related to changes in FSH, testosterone or testis length; and 2) whether castration and(or) estradiol implants affected plasma concentrations of INH and FSH. In Exp. 1, plasma INH remained constant from 4 until 8 wk of age then increased from 120 pM to 202 pM between 8 and 12 wk. Thereafter, INH decreased to 90 pM by 36 wk. Between 4 and 10 wk, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 22 publications
4
8
1
2
Order By: Relevance
“…These findings are consistent with a previous report that bull calves secreted significant amounts of inhibin into the plasma during the infantile and prepubertal stages of development [9]. Moreover, there was a clear negative relationship between serum levels of inhibin and FSH.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are consistent with a previous report that bull calves secreted significant amounts of inhibin into the plasma during the infantile and prepubertal stages of development [9]. Moreover, there was a clear negative relationship between serum levels of inhibin and FSH.…”
Section: Discussionsupporting
confidence: 82%
“…This is a similar pattern to that reported previously in rams (Schanbacher 1988, Isaacs et al 1995 and in bulls (Miyamoto et al 1989, MacDonald et al 1991 and male rats (Crofton et al 1997) but is different to that found in male monkeys (Keeping et al 1990, Marson et al 1993 and boys (Burger et al 1988, Crofton et al 1997. Nonetheless, a recent study in boys using a specific assay for inhibin B has shown that levels of this hormone are high in the first year of life (Andersson et al 1997).…”
Section: Discussionsupporting
confidence: 73%
“…The testes of prepubertal males synthesize and secrete significant amounts of inhibin and the pattern of secretion of inhibin changes during sexual development although there appears to be substantial differences between species. For example, circulating concentrations of inhibin during sexual maturation have been found to increase in male monkeys (Keeping et al 1990, Marson et al 1993) and in boys (Burger et al 1988, Crofton et al 1997 but to decrease in male rats (Wreford et al 1994), bulls (Miyamoto et al 1989, MacDonald et al 1991 and rams (Schanbacher 1988, Isaacs et al 1995. Several studies indicate that a functional negative feedback system between inhibin and FSH exists before puberty as shown by the decrease in plasma concentrations of inhibin and an increase in FSH in 1-week-old ram lambs (Schanbacher 1988), and the demonstration that active immunization against inhibin in prepubertal ram lambs (Al-Obaidi et al 1987) and bull calves (Martin et al 1991, Schanbacher 1991 caused an increase in plasma concentrations of FSH.…”
Section: Introductionmentioning
confidence: 99%
“…Os níveis de LH na circulação perifé-rica apresentaram crescimento gradual, mas consistente, da 10 a a 30 a semanas, estabilizando-se a partir de então (Figura 7). Estes padrões de secreção de FSH e LH são similares aos observados anteriormente em touros (MacDonald et al, 1991;Chandolia et al, 1997;. Embora o FSH tenha reconhecidamente efeito estimulador sobre a mitose das células de Sertoli (Buzzard et al, 2002;Sharpe et al, 2003), este hormônio também contribui com o processo de diferenciação (Dorrington et al, 1979;Walker & Cheng, 2005) e a síntese de fatores de crescimento pelas células de Sertoli, os quais promovem a maturação das células de Leydig (Sharpe, 1994;Walker & Cheng, 2005), tornando-as aptas a responder aos Tabela 2 -População de células Sertoli e germinativas por secções transversais de túbulos seminíferos em touros Angus em diferentes idades Figura 5 -Túbulos seminíferos de touros Angus de 26 semanas de idade, em seção transversal (1.000 x).…”
Section: Resultsunclassified